Outcomes of CMML patients undergoing allo-HCT are significantly worse compared to MDS-a study of the CMWP of the EBMT - Rovó, Alicia; Gras, Luuk; Piepenbroek, Brian; Kroeger, Nicolaus; Reinhardt, H. Christian; Radujković, Aleksandar; Blaise, Didier; Kobbe, Guido; Niityvuopio, Riitta; Platzbecker, Uwe; Sockel, Katja; Hunault-Berger, Mathilde; et al. (American journal of hematology, 2024)
Although CMML since long has been separated from MDS, many studies continue to evaluate the outcomes of both diseases after hematopoietic cell transplantation (allo-HCT) together. Data evaluating outcomes of a large CMML cohort after allo-HCT compared to MDS are limited. We aim to compare outcomes of CMML to MDS patients who underwent allo-HCT between 2010 and 2018. Patients >= 18 years with CMML and MDS undergoing allo-HCT reported to the EBMT registry were analyzed. Progression to AML before allo-HCT was an exclusion criterion. Overall survival (OS), progression/relapse-free survival (PFS), relapse incidence (including progression) (REL), and non-relapse mortality (NRM) were evaluated in univariable and multivariable (MVA) Cox proportional hazard models including interaction terms between disease and confounders. In total, 10832 patients who underwent allo-HCT were included in the study, there were a total of 1466 CMML, and 9366 MDS. The median age at time of allo-HCT in CMML (median 60.5, IQR 54.3-65.2 years) was significantly higher than in the MDS cohort (median 58.8, IQR 50.2-64.5 years; p < .001). A significantly higher percentage of CMML patients were male (69.4%) compared to MDS (61.2%; p < .001). There were no clinically meaningful differences in the distribution of Karnofsky score, Sorror HCT-CI score at allo-HCT, and donor type, between the CMML and MDS patients. RIC platforms were utilized in 63.9% of CMML allo-HCT, and in 61.4% of MDS patients (p = .08). In univariable analyses, we found that OS, PFS, and REL were significantly worse in CMML when compared with MDS (all p < .0001), whereas no significant difference was observed in NRM (p = .77). In multivariable analyses, the HR comparing MDS versus CMML for OS was 0.81 (95% CI, 0.74-0.88, p < .001), PFS 0.76 (95% CI 0.70-0.82, p < .001), relapse 0.66 (95% CI 0.59-0.74, p < .001), and NRM 0.87 (95% CI 0.78-0.98, p = .02), respectively. The association between baseline variables and outcome was found to be similar in MDS and CMML (all interaction p > .05) except for a decreasing trend over time of the risk of relapse in CMML (HR allo-HCT per year later 0.94, 95% CI 0.90-0.98), whereas no such trend was observed in MDS (HR 1.00, 95% CI 0.98-1.02). The poor outcome observed for CMML could be related to variables not measured in this study or to factors inherent to the disease itself. This study demonstrates that outcomes of CMML patients after allo-HCT are significantly worse compared to MDS. The results of this study may contribute to future recommendations for allo-HCT in CMML patients.